Analysis of the Acceptance of Audit Opinion (A Case Study on Infrastructure, Utilities and Transportation Companies in Indonesia) - Suryandari, Dhini; Kiswanto, Kiswanto; Ningrum, Tri Sulistya (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2018)
This study aims to determine the effect of corporate governance (CG) mechanisms and the size of the company on the acceptance of Fair with Exception (WDP) opinion. The population of this research is a number of 212 infrastructure, utility and transportation sector companies on the Indonesia Stock Exchange from 2012-2015. The sample was selected using purposive sampling and produced 88 observation units. The method of data used in this study is the logistic regression method. Data analysis shows two Corporate Governance mechanisms, namely the existence of the board of directors and the board of commissioners does not affect the acceptance of WDP opinion. On the other hand, the existence of independent commissioners and audit committees can influence the acceptance of WDP audit opinions. The conclusion of this study is that the presence of supporting bodies provides a positive injection for the company and affects the company’s accounting for the better.